Impact of comprehensive family history and genetic analysis in the multidisciplinary pancreatic tumor clinic setting. (30th July 2022) - Everett, Jessica N.; Dettwyler, Shenin A.; Jing, Xiaohong; Stender, Cody; Schmitter, Madeleine; Baptiste, Ariele; Chun, Jennifer; Kawaler, Emily A.; Khanna, Lauren G.; Gross, Seth A.; Gonda, Tamas A.; Beri, Nina; et al.
Abstract: Background: Genetic testing is recommended for all pancreatic ductal adenocarcinoma (PDAC) patients. Prior research demonstrates that multidisciplinary pancreatic cancer clinics (MDPCs) improve treatment‐ and survival‐related outcomes for PDAC patients. However, limited information exists regarding the utility of integrated genetics in the MDPC setting. We hypothesized that incorporating genetics in an MDPC serving both PDAC patients and high‐risk individuals (HRI) could: (1) improve compliance with guideline‐based genetic testing for PDAC patients, and (2) optimize HRI identification and PDAC surveillance participation to improve early detection and survival. Methods: Demographics, genetic testing results, and pedigrees were reviewed for PDAC patients and HRI at one institution over 45 months. Genetic testing analyzed 16 PDAC‐associated genes at minimum. Results: Overall, 969 MDPC subjects were evaluated during the study period; another 56 PDAC patients were seen outside the MDPC. Among 425 MDPC PDAC patients, 333 (78.4%) completed genetic testing; 29 (8.7%) carried a PDAC‐related pathogenic germline variant (PGV). Additionally, 32 (9.6%) met familial pancreatic cancer (FPC) criteria. These PDAC patients had 191 relatives eligible for surveillance or genetic testing. Only 2/56 (3.6%) non‐MDPC PDAC patients completed genetic testing ( p < 0.01). Among 544 HRI, 253 (46.5%) had a known PGV or a designation of FPC, and were eligible for surveillance at baseline; of the remainder, 15/291 (5.2%) were eligible following genetic testing and PGV identification. Conclusion: Integrating genetics into the multidisciplinary setting significantly improved genetic testing compliance by reducing logistical barriers for PDAC patients, and clarified cancer risks for their relatives while conserving clinical resources. Overall, we identified 206 individuals newly eligible for surveillance or genetic testing (191 relatives of MDPC PDAC patients, and 15 HRI from this cohort), enabling continuity of care for PDAC patients and at‐risk relatives in one clinic. Abstract : Genetic testing is recommended for all pancreatic ductal adenocarcinoma (PDAC) patients. Limited information exists regarding the utility of integrated genetics in the multidisciplinary pancreatic cancer clinic setting. We found that integrating genetics into the multidisciplinary setting significantly improved genetic testing compliance by reducing logistical barriers for PDAC patients, and clarified cancer risks for their relatives while conserving clinical resources.